2014
DOI: 10.1111/bcpt.12248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UGT2B7,OPRM1 and ABCB1 Gene Polymorphisms on Postoperative Morphine Consumption

Abstract: Therapeutic modulation of pain with morphine and other opioids is associated with significant variation in both effects and adverse effects in individual patients. Many factors including gene polymorphisms have been shown to contribute to the interindividual variability in the response to opioids. The aim of this study was to investigate the significance of UGT2B7, OPRM1 and ABCB1 polymorphisms for interindividual variability in morphine-induced analgesia in patients undergoing hysterectomy. The frequency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…It has been speculated that the absorption of morphine is reduced in the CC carriers due to the effective efflux by P-gp in gut and/or through the blood brain barrier and consequently reducing the bioavailability of morphine for the receptors in brain. Conversely the TT carriers with abnormal function of P-gp should have a higher concentration of morphine [16]. The C3435T ABCB1 SNP has recently been associated with a different need for morphine in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that the absorption of morphine is reduced in the CC carriers due to the effective efflux by P-gp in gut and/or through the blood brain barrier and consequently reducing the bioavailability of morphine for the receptors in brain. Conversely the TT carriers with abnormal function of P-gp should have a higher concentration of morphine [16]. The C3435T ABCB1 SNP has recently been associated with a different need for morphine in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that genetic polymorphisms of drug transporters are the cause for variations in pain sensitivity shown not just in animal studies but also in humans . There are very few, if any, reported studies of pain sensitivity, especially of cold pain, among healthy subjects in association with the ABCB1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of P‐gp activity enhanced the analgesic effects of opioids due to its increase in the brain concentration . Bastami et al showed that ABCB1 gene polymorphisms were significantly associated with variability in morphine drug requirements in 40 patients undergoing abdominal hysterectomy. It was found that patients homozygous for 1236T and 3435T alleles required lower doses of morphine for pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other similar study approaches reveal no such relationship [2,3]. Moreover, no significant results have been found in human experimental pain models and controlled clinical-pain models [1,2,4]. This could be due to poor study designs lacking relevant end points (e.g., side effects and pharmacodynamic response).…”
Section: Polymorphisms Affecting Drug Transportersmentioning
confidence: 97%